A rare symptomatic presentation of ecchordosis physaliphora: neuroradiological and surgical management. Issue 6 (8th January 2007) - Rotondo, M; Natale, M; Mirone, G; Cirillo, M; Conforti, R; Scuotto, A
Abstract : We report a case of ecchordosis physaliphora, an uncommon benign lesion originating from embryonic notochordal remnants, intradurally located in the prepontine cistern, that unusually presented associated with symptoms. MRI detected and precisely located the small mass. At surgery, a cystic gelatinous nodule was found ventral to the pons, contiguous with the dorsal wall of the clivus via a small pedicle. Histological examination diagnosed the lesion as an ecchordosis physaliphora. Here we focus on the analysis of the neuroradiological aspects that play a crucial role from both a diagnostic and a therapeutic standpoint.